THE EFFECT OF EDUCATION, GENDER, AND EMPLOYMENT STATUS ON THE INCOME OF WORKERS IN BALI - Bhaskara, Anak Agung Yoga (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 9 (2019): Vol. 8, No.9, September 2019, pp (1947-2194), 2019)
The succes of development can be measured by the level of welfare of the population. The level of welfare is identical with income, if the income of the community is high, then the level of welfare is also high. The level of income is influenced by several factors such as education, gender and employment status. The level of well-being can also be seen from prevalence of income distribution. But in Bali Province the income distribution is still not evenly ditributed between districts and cities with each other. The purpose of this studi was to determine the effect of simultaneous or partial education, gender, and employment status on the income of workers in Bali Province. This study uses multiple linier regression analysis and uses primary data. Based on the result of testing, simultaneous education, gender, and employment status simultaneously affect the income of workers in Bali Province. Partially education, gender, and employment status have a positive and significant effect on the income of workers in Bali Province.